The long run impact of biofuels on food prices - Ujjayant Chakravorty; Marie-Hélène Hubert; Michel Moreaux; Linda Nøstbakken (Center for Economic Studies and ifo Institute (CESifo), 2012)
More than 40% of US grain is now used to produce biofuels, which are used as substitutes for gasoline in transportation. Biofuels have been blamed universally for recent increases in world food prices. Many studies have shown that these energy mandates in the US and EU may have a large (30-60%) impact on food prices. In this paper we show that demand-side effects - in the form of population growth and income-driven preferences for meat and dairy products rather than cereals - may play as much of a role in raising food prices as biofuel policy. By specifying a Ricardian model with differential land quality, we show that a significant amount of new land will be converted to farming which is likely to cause a modest increase in food prices. However, biofuels may increase aggregate world carbon emissions, due to leakage from lower oil prices and conversion of pasture and forest land for farming.
Keywords: Q24; Q32; Q42; 330; clean energy; food demand; land quality; renewable fuel standards; transportation; Biokraftstoff; Landwirtschaftliche Bodennutzung; Nahrungsmittelpreis; Verkehrsökologie; Theorie